2013
DOI: 10.1080/09658211.2013.791321
|View full text |Cite
|
Sign up to set email alerts
|

The longevity of adaptive memory: Evidence for mnemonic advantages of survival processing 24 and 48 hours later

Abstract: Prior studies have convincingly demonstrated that survival-related processing of information enhances its subsequent retention. This phenomenon, known as the survival recall advantage, generalises to other stimuli, memory domains, and research populations, thereby underscoring its reliability. As previous studies used only short retention intervals between survival processing and the memory test, an important yet hitherto unanswered issue is whether this effect persists over time. The present experiment theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
(33 reference statements)
3
21
0
Order By: Relevance
“…However, few studies have investigated its longevity with language based stimuli (Raymaekers et al, 2014;Abel & Bäuml, 2013) and no studies have explored the effect duration in location memory. The results of our study show that the survival processing advantage is still present 4 days after encoding in both language based and location memory.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, few studies have investigated its longevity with language based stimuli (Raymaekers et al, 2014;Abel & Bäuml, 2013) and no studies have explored the effect duration in location memory. The results of our study show that the survival processing advantage is still present 4 days after encoding in both language based and location memory.…”
Section: Discussionmentioning
confidence: 99%
“…A four day delay was chosen based on Ebbinghaus' (1964) suggestion that the majority of forgetting occurs during the first 4-5 days after encoding. In Experiment 1, we attempted to replicate and transpose the findings of Raymaekers et al (2014) and Abel and Bäuml (2013) to a longitudinal paradigm using word lists as target stimuli. We predicted that a comparable pattern of recall to Raymaekers et al (2014) and Abel and Bäuml (2013) would be observed.…”
Section: Downloaded By [Liverpool Hope University] At 05:02 04 Augustmentioning
confidence: 99%
See 3 more Smart Citations